PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP MINAT KUNJUNG PENGUNJUNG DI HANANIA BEACH AND RESTO KOTA DUMAI - Hapsary, Rifka Afifa; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research aims to explore in depth the use of Instagram social media as a promotional tool at Hanania Beach and Resto, Dumai, and analyze its impact on tourist interest in visiting this destination. This research uses a quantitative approach, where the population studied is the followers of the official Hanania Beach and Resto Instagram account. The data needed in this research was collected through various methods, namely direct observation of promotional activities on social media, distribution of questionnaires to followers of Instagram accounts, as well as documentation related to uploads and interactions on the platform. Based on the results of data analysis, this research shows that the use of Instagram has significant potential as a promotional medium. This is supported by the results of data processing which show that the tcount value is higher than ttable, with the significance level being below the predetermined threshold. These findings indicate that there is a strong relationship between promotional intensity via Instagram and increased tourist interest in visiting Hanania Beach and Resto. Thus, H0 which states there is no influence is rejected, while Ha which states there is a positive influence is accepted. Keywords: Instagram Social Media, Interest in Visiting Tourists, Hanania Beach and Resto